Optimizing the Construction Supply Chain Network Considering the Flow of Materials, Equipment, Manpower, Drawings and Technical Documents - Seyed Saeid Helli; Hadi Mokhtari; Saeed Dehnavi (پژوهش در مدیریت تولید و عملیات, 2024)
Purpose: Today, the efficient management of supply chains plays a fundamental role in the market and economy. The supply chain is a network of facilities working together to make and move products from upstream to downstream to provide customers with highly qualified products and services. Nowadays, construction has become a growing and huge industry sector worldwide. One of the supply chains that needs proper management is related to the construction industry. The purpose of this article is to optimize this type of supply chain by minimizing its total costs. Design/methodology/approach: An attempt has been made to develop an optimization model for the construction supply chain, considering all the important elements involved in the construction process, i.e. contractors, designers, suppliers of materials and construction materials, as well as three important and basic flows in the construction industry, i.e. the flow of manpower, the flow of equipment and machinery, and the flow of materials. All indices, parameters, decision variables, objective functions and constraints have been introduced and presented in the proposed model. Findings: The model proposed by GAMS optimization software was solved and the obtained results included the lowest construction cost as well as the optimal amount of construction materials and materials, labour, equipment, and machinery based on the required construction size. Research limitations/implications: The application of the supply chain in the construction industry is a relatively new topic. In the classic supply chain, the flow of materials and output at the end of the chain includes the manufactured product, while in the construction supply chain, the final output includes a building or a structure. Individuals, industries and even countries incur a lot of construction costs to meet their needs in the field of construction. The current study was influenced by limitations such as access to real data and the impossibility of handling a real case study, because the problem of designing the construction supply chain has wide dimensions and requires access to all dimensions of the construction industry chain, from upstream to downstream. Practical implications: With the definition and expansion of the concept of supply chain and the use of supply chain management in manufacturing industries and the positive results it brought in various manufacturing industries, supply chain management emerged in the construction industry. Meanwhile, researchers, major contractors, and large construction companies are trying to find methods to take advantage of the supply chain management approach. Also, the stakeholders of the construction industry can enable active decision-making and agile responses to market fluctuations by continuously monitoring and updating the results of cost sensitivity analysis. Social implications: Optimizing the construction supply chain can lead to reduced costs, improved project timelines, and enhanced sustainability. However, it may also impact local communities through job displacement, environmental concerns, and social inequality. Balancing efficiency with social responsibility is crucial to ensure equitable outcomes in construction projects. Originality/value: By now, there has been no reference available in the literature in the field of construction supply chain considering the designer, the flow of manpower and the flow of drawings and technical documents. The proposed model is comprehensive and includes the construction chain, considering all aspects such as the flow of required materials and materials, the flow of labour, the flow of required equipment and machinery, the flow of plans and documents, and designers and contractors.